"I Am Because We Are": Exploring Women's Leadership Under Ubuntu Worldview. (May 2016) - Ngunjiri, Faith Wambura
The Problem: Although there are women leading in various sectors within African societies and institutions, very little research has been done to explore and explain their experiences within their cultural, economic, social, historical, and political context. To have a deeper understanding of women's leadership globally, there must be studies of women's leadership within specific local contexts. The Solution: This article explicates women's leadership under the ubuntu worldview, with implications for application in contemporary organizations beyond the African context. Ubuntu reflects the African understanding of the essence of humanity. Guided by Black feminist theorizing, the study employed portraiture qualitative approach; in-depth interviews with women leaders provided illustrative quotes about spirituality, interdependence, unity, and community building. The Stakeholders: The article is aimed at both leadership scholars and leadership training practitioners with a focus on the African context.